Development and application of an updated haplotype reference panel for association analysis of spontaneous sex reversal in XX rainbow trout - Liu, Sixin; Weber, Gregory M.; Martin, Kyle E.; Long, Roseanna; Birkett, Jill E.; Palti, Yniv (Frontiers in Genetics, 2025)
With the rapid cost reduction of next-generation sequencing, low-coverage whole-genome sequencing (lcWGS) followed by genotype imputation is becoming a cost-effective alternative to SNP (single nucleotide polymorphism) array genotyping. Previously, we constructed a reference panel consisting of 410 samples representing five breeding populations of rainbow trout (Oncorhynchus mykiss). However, the reference panel had a limited representation of the major commercial populations in the U.S. The objectives of this study were two-fold: 1) to update the haplotype reference panel of rainbow trout by adding more reference populations and more samples from the previous reference populations; and 2) to identify SNPs associated with spontaneous sex reversal to males in XX rainbow trout (sXX sex reversal). To update the reference panel, high-coverage whole-genome sequences were obtained from 129 additional fish from several populations. To identify SNPs associated with sXX sex reversal, samples from two families were genotyped with both the Axiom 57K SNP array and lcWGS. The updated reference panel outperformed the previous panel with an increase in accuracy of genotype imputation and a reduction in low-confidence genotypes. Based on the array genotypes, 55 significant SNPs associated with sXX sex reversal were identified and 53 out of the 55 SNPs were located on chromosome OmyA26. Based on the imputed genotypes, 743 SNPs on chromosome OmyA26 and 7 SNPs on chromosome OmyA19 were associated with sXX sex reversal. Two of those OmyA26 significant SNPs were identified by both genotyping methods. In conclusion, the updated haplotype reference panel improved the accuracy of genotype imputation from lcWGS, and enabled identification of additional SNPs associated with sXX sex reversal in rainbow trout.